Pengaruh Aktivitas Budaya Keramba Jaring Apung Terhadap Kualitas Air Sungai Mempawah - Sinurat, Merry Ananda Pratiwi; Utomo, Kiki Prio; Desmaiani, Herda (Jurnal Teknologi Lingkungan Lahan Basah, 2024)
The Mempawah River is a water source used by the people of Mempawah Regency and plays an important role in supporting life. One of the community activities as a means of livelihood is fishing activities, namely fish cultivation. Effluent or waste from cultivation activities goes directly into the river body. This causes the entry of polluted materials such as organic materials originating from feed remains, feces and fish urine into the river body and can affect river water quality parameters. Increasing the concentration of organic matter in water can have an impact on reducing water quality. One of them is increasing BOD concentration. This research aims to determine the BOD concentration in waters, calculate the pollution load. The results of the research show that there is a BOD concentration value that is above the class II river water quality standard according to Government Regulation Number 22 of 2021.